Indoor hockey officials' noise exposure, temporary hearing loss, and effect of helmet visor length on exposure to whistle noise - Adams, Karin L., author; Brazile, William, advisor; Reynolds, Stephen, committee member; Peel, Jennifer, committee member; Legare, Marie, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.